Comparison between patients with thyroid follicular tumors in the histological pattern and size of follicular lesion - Ban Jumaah Qasim; Wijdan Basheer Abid; Buthainah Ibraheem Hameed Al-Ezzi; Zahraa Ahmed Okhti (College of Pharmacy / Mustansiriyah University, 2018)
The main problem encountered in thyroid nodule is difficult to differentiate between a benign and malignant lesion. Differential between follicular thyroid cancer (FTC) and benign follicular thyroid adenoma (FTA) is a great challenge for even an experienced pathologist and requires special effort. A total of 120 paraffin block were included in the study, 30 blocks were (FC), 30 blocks were (FVPC). 30 blocks were (FA), 30 blocks were blocks thyroid follicular hyperplasia.20 blocks endocervical epithelium.20 paraffin blocks of colonic epithelium as control. From each paraffin block, 4 slides, each of thicken were taken, stained with Hematoxylin and Eosin (H&E) for revision of histopathological diagnosis. The histological arrangement in follicular carcinoma and follicular adenoma was significant (P= 0.001) in trabecular pattern and the difference was significant (P= 0.016) in mixed pattern while no significance with microfollicular, macrofollicular and normofollicular pattern in both follicular carcinoma and adenoma. There was no significant difference in size follicular lesion among FA, FVPC and follicular hyperplasia (P> 0.05) while, the size follicular lesion in of (FC) was significantly higher from all other groups (P< 0.05).